Rare bird documentation form for Glaucous Gull at Lake Manawa, 1978 - Bray, Tanyaet al; Kovanda, Sandraet al; Padelford, Babset al (1978)
Rare bird documentation form for a Glaucous Gull at Lake Manawa in Pottawattamie County, IA on December 6, 1978. Epson - sheet feed